Grand challenges: reflections on the future of community corrections - Taxman, Faye S. (The Routledge handbook on global community corrections, 2024)
Our review of how community corrections systems are structured, implemented, and evaluated in 20 different countries around the world highlights both the similarities and differences in these systems, which we examine in six analytic chapters included in Section 2 of this Handbook. Our analyses produce insights regarding the size, composition, and goals of community corrections systems. They reveal difficulties faced by policymakers, practitioners, and researchers alike, such as lack of routinely collected and/or publicly available data. Almost universally, there is a failure to recognize probation as an entity that serves a specific purpose, not just an entity in lieu of prison. As community corrections expands and evolves around the world, such difficulties will continue to impact these systems and those within them. Thus, we offer four Grand Challenges for community corrections—aspirational goals that are difficult to achieve, inspire, and demand collective efforts and cooperation: (1) establish community corrections as a standalone sanction focused on desistance and rehabilitation, (2) support desistance-focused community corrections through relationship-building, culture change, and community support, (3) promote fair and just treatment for individuals on supervision and those who work in the field of community corrections, and (4) invest in individuals, families, communities, and community corrections to foster desistance and rehabilitation. These grand challenges are set forth to galvanize the global community to strengthen community corrections to serve a clear sentencing purpose.